Retrospective Outcome Analysis of Geriatric Traumatic Brain Injury Treated at a Tertiary Care Center in India - Kumar, Abhishek; Jaiswal, Somil; Ojha, B.K.; Chandra, Anil; Srivastava, Chhitij; Bajaj, Ankur; Yadav, Awdhesh (Indian Journal of Neurosurgery, 2024)
Trauma is a major cause of morbidity and mortality in elderly patients and its management is challenging. Outcome assessment in these patients is difficult because of preexisting chronic medical conditions as it may be impossible to isolate the effect of traumatic brain injury. This study aimed to examine the clinical outcomes and epidemiological and clinicoradiological characteristics of geriatric traumatic brain injury patients at a tertiary care center.The clinical records of patients aged ≥60 years with head injuries treated at King George's Medical University between 2016 and 2020 were included in the study. Patients were followed up in the outpatient department or through telephone consultation. The follow-up period was updated using the Glasgow outcome score (GOS) of patients for current neurological status and relevant radiological investigations.The mean age of subjects was 66.16 ± 6.55 years. Road traffic accidents were the most frequent cause of brain injuries (448 [68.5%]). In total, 41% of the study patients had severe head injuries (Glasgow coma scale, GCS < 9) at admission. The in-hospital mortality was 25.2%. In total, 60.7% of discharged patients showed favorable outcomes (GOS: 4 or 5). GCS at admission, best motor response, and associated comorbidity (diabetes mellitus) significantly predicted the outcome at 6 months. The majority of the patients (82.6 %) were 60 to 70 years of age.Road traffic accidents are the most frequent cause of brain injuries in geriatrics. Most of them were managed medically, and majority were discharged (74.8%). Out of those discharged, 39.3% had unfavorable outcomes.
Keywords: Glasgow outcome score; comorbidity; traumatic brain injury; hematoma; hospital stay